La procedencia efectiva de la institución del abandono y su efecto en el descongestionamiento de causas civiles - Rosero Ruilova, Isaí Franklin (2022)
In the work presented, the study and analysis of the Institute of Abandonment is carried out, both its legal reforms, legislation, legal procedure, regulations, term deadlines and theoretical references of which are substantially related to the decongestion of civil judicial cases, highlighting its object and main characteristic, which is the extraordinary conclusion of judicial processes, emphasizing the need for which the current reality of the civil judicial system is found, being the decongestion of civil cases. Taking into account the aforementioned, it is a fundamental priority on the part of the State to guarantee the speed and procedural economy by promoting the decongestion of civil judicial cases, in accordance with this way the institution of Abandonment as a solution path, as long as the effective provenance is carried out of the same, as the main means of decongesting judicial cases...........